The Knowledge and Skills of Nutritional Menu Preparation Among Toddler Mother - Apris Sureni Rahayu; Diyah Yulistika Handayani (UM Purwokerto Press, 2022)
Background: In Indonesia, the proportion of toddlers having nutritional issues in 2018 was 17.7%. In contrast, in Central Java, malnutrition among toddlers was 1.1% frequent, and inadequate nutrition among toddlers was 5.0% in 2020. According to the Banyumas District Health Office report, there were 6,638 people who needed to improve their diet immediately. In the working area of Kalibagor Public Health Care Center, 69 toddlers had low nutrition and 12 had malnutrition. Objective: The purpose of this research is to find out the nutrient knowledge and skill of toddlers’ mothers before and after the training of toddlers’ nutritional menu processing in the working area of Kalibagor Public Health Care Center, Banyumas District. Method: The method of this research was pre-experimental design with one group pre-test and post-test design. The samples included 45 mothers who were selected using the Slovin formula, and the population included 81 mothers whose children had low malnutrition. Results: The mothers' knowledge and competence level in planning and digesting their toddlers' diets were the variables that were measured. It indicated that the degree of ability and knowledge had a significant effect (p=0.000). Conclusion: Thus, it can be concluded that providing training on toddler nutrition has a favorable impact on a mother's skills. The next researcher is expected to explore social and cultural elements in order to improve respondents' knowledge and skills.